TANTANGAN KOORDINASI KELEMBAGAAN DP3AP2KB DALAM PELAKSANAAN PENGARUSUTAMAAN GENDER DI KABUPATEN JEPARA - Seifaa Azallea Efendi; Kismartini Kismartini (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
Gender Mainstreaming is a development strategy that requires effective institutional coordination to ensure proper implementation. This article aims to analyze the challenges of institutional coordination within DP3AP2KB in implementing Gender Mainstreaming in Jepara Regency. The study employed a descriptive qualitative approach, with data collected through interviews, observation, and documentation. The analysis used Potter and Brough’s Systemic Capacity Building theory, focusing on role capacity, structural capacity, and systems capacity. The findings show that DP3AP2KB’s institutional coordination has been supported by the division of tasks, organizational structure, coordination forums, and reporting systems. However, its implementation remains suboptimal because Gender Mainstreaming is still concentrated in the PPPA Division, the effectiveness of coordination forums and follow-up actions is inconsistent, and standardized procedures are not yet fully established. Therefore, the main challenge lies in the weak integration of roles, coordination structures, and work systems in supporting the consistent implementation of Gender Mainstreaming.